Stopping Smokeless Tobacco Use: A Call to Action - Reed, Donald; Bowen, Elaine; Fint-Clark, Becca; Clark, Brent; Cobb, Nila; Danberry, Kathy M.; Hutson, Zona; Lusk, Stephanie; Rine, Jason; Robinson, Natasha (Frontiers in Public Health, 2021)
Smokeless tobacco use and dual tobacco use is increasing in the United States. Many tobacco prevention resources and funding are targeted toward cigarette smoke. This is problematic, as tobacco companies are marketing new dissolvable tobacco products in the United States. New data suggested that smokeless tobacco use is increasing in West Virginia and across the nation. In order to address this issue, the West Virginia Extension Service partnered with the West Virginia Department of Health and Human Resources’ Division of Tobacco Prevention to develop a comprehensive spit tobacco curriculum targeting 3rd through 6th graders throughout West Virginia. This article details the development and assessment of the spit tobacco prevention curriculum and the report from the initial pilot of the program. The curriculum was piloted through six counties in schools, after school programs and 4-H clubs. Survey results after implementation show that youth have increased awareness in smokeless tobacco. Throughout the article, we explore West Virginia’s Cooperative Extension Service’s response to this emerging public health issue and putting out a call to action for the National Cooperative Extension Services to become involved in spit tobacco prevention.